USING THE METHOD OF GROUP TRAINING OF MECHANICAL STUDENTS - Кісєтов, Юрій (SWorldJournal, 2024)
The modern educational process using problem-based learning methods allows you to get the necessary training for the successful work of specialists in the future. The paper analyzes the experience of implementing a modern approach to the professional and